Application of Neural Network on Generating Power Forecasting for PV System - 刘敬; 高志建 (Kongzhi Yu Xinxi Jishu)
Output of photo-voltaic (PV) system is influenced by unconstant solar radiation. In order to forecast the power output of PV system as accurately as possible, a method of solar quantity estimation is required. Therefore, it is proposed a method of neural network to estimate solar quantity, and the rationality is confirmed by computer simulations. Then three kinds of neural networks: FFNN, RBFNN and RNN are introduced, and finally the simulation results are properly compared.